Extension of the Freiberg Layer Model by Means of Elastic–Plastic Material Behavior. Issue 4 (28th October 2021) - Weiner, Max; Schmidtchen, Matthias; Prahl, Ulrich
Abstract : Finite element method simulations offer deep and detailed modeling of complex processes, but with high effort of computation power and time. For the special purpose of flat rolling, a layer model was developed by Schmidtchen before based on the classic elementary theory of plasticity with the purpose to model inhomogeneous behavior with significant lower effort at computation. This model considered the layers only as rigid or in plastic deformation state. Herein, the model is extended by elastic material behavior to get closer to the depth of finite elements method (FEM) models. The results are first compared with a FEM simulation and measurements from the literature. The current model is found to fit well the FEM results as well as the measurements. Second, the results are compared with classic elementary theory and the layer model of Schmidtchen. From these comparisons is found, that the main elastic influences on the stress curve shape are due to the full elastic zones. Elastic deformations in the plastic regions are found to be smaller, but growing on transition from block rolling to thin sheet rolling. Abstract : For flat rolling simulation generally two approaches exist: the elementary theory or slab method, as well as the finite element method. Finite element method‐based simulation offer deep and accurate modeling but with high effort in computation. Herein, a slab method based layer model by Schmidtchen is extended by elastic‐plastic material behavior and evaluated in comparison to FEM. Herein, the model is extended by elastic–plastic material behavior and evaluated in comparison with FEM.